Label‐free quantitative proteomic and phosphoproteomic analyses of renal biopsy tissues in membranous nephropathy. Issue 1 (29th September 2021) - Li, Shanshan; Luo, Zhifeng; Meng, Shuhui; Qiu, Xiaofen; Zheng, Fengping; Dai, Weier; Zhang, Xinzhou; Sui, Weiguo; Yan, Qiang; Tang, Donge; Dai, Yong
Abstract: Purpose: Membranous nephropathy (MN) is a common cause of nephrotic syndrome in adults. However, the underlying mechanisms of its occurrence and development are not completely clear. Thus, it is essential to explore the mechanisms. Experimental design: Here, we employed label‐free quantification and liquid chromatography‐tandem mass spectrometry analysis techniques to investigate the proteomic and phosphoproteomic alterations in renal biopsy tissues of MN patients. Samples were collected from 16 MN patients and 10 controls. Immunohistochemistry (IHC) was performed to validate the hub phosphoprotein. Results: We focused on the changes in the phosphoproteome in MN group versus control group (CG). Totally, 1704 phosphoproteins containing 3241 phosphosites were identified and quantified. The phosphorylation levels of 216 phosphoproteins containing 297 phosphosites were differentially regulated in stage II MN group versus CG, and 333 phosphoproteins containing 461 phosphosites were differentially phosphorylated in stage III MN group versus CG. In each comparison, several differential phosphoproteins were factors, kinases and receptors involved in cellular processes, biological regulation and other biological processes. The subcellular location of most of the differential phosphoproteins was the nucleus. Protein–protein interaction analysis showed that the connections among the differential phosphoproteins were extremely complex, and several signalling pathways probably associated with MN were identified. The hub phosphoprotein was validated by IHC. Conclusions and clinical relevance: This investigation can provide direct insight into the global phosphorylation events in MN group versus CG and may help to shed light on the potential pathogenic mechanisms of MN.